1969
DOI: 10.1002/pen.760090509
|View full text |Cite
|
Sign up to set email alerts
|

The effect of aspect ratio on the fatigue life of short boron fiber reinforced composites

Abstract: The flexural fatigue characteristics of boron fiber reinforced epoxy were shown to be strongly dependent on the aspect ratio of the reinforcing fibers. These composites were evaluated in a stiffness limited, constant maximum stress mode. The failure mechanism was found to be a combination of interfacial failure and brittle rupture of the matrix at 45 deg to the axis of the fibers. These fatigue cracks result in debonding of the outer fibers, thereby reducing the effective moment of inertia of the specimen.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
6
0

Year Published

1982
1982
2024
2024

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 29 publications
(6 citation statements)
references
References 5 publications
0
6
0
Order By: Relevance
“…In a study by Lavengood and Gulbransen on a short boron fiber epoxy composite [4], fatigue strength was found to increase with increased fiber length and reach a plateau at a particular fiber aspect ratio. An optimum nominal fiber length depending on fiber content and molding conditions can be used to improve fatigue performance.…”
Section: Introductionmentioning
confidence: 95%
“…In a study by Lavengood and Gulbransen on a short boron fiber epoxy composite [4], fatigue strength was found to increase with increased fiber length and reach a plateau at a particular fiber aspect ratio. An optimum nominal fiber length depending on fiber content and molding conditions can be used to improve fatigue performance.…”
Section: Introductionmentioning
confidence: 95%
“…The fiber-reinforced coatings studied in this paper were incorporated with milled carbon fibers, instead of typical long fibers to produce an isotropic response to the impacting particles, also providing a discontinuous path for impacting energies. However, the introduction of milled carbon fibers came with a tradeoff of using a lower aspect ratio (length/depth) of the fibers, and higher aspect ratios are indicated to have greater fatigue resistance . Generally, the erosion process on fiber-reinforced elastomeric composite seems to take place in two modes .…”
Section: Results and Discussionmentioning
confidence: 99%
“…However, the introduction of milled carbon fibers came with a tradeoff of using a lower aspect ratio (length/depth) of the fibers, and higher aspect ratios are indicated to have greater fatigue resistance. 42 Generally, the erosion process on fiber-reinforced elastomeric composite seems to take place in two modes. 25 First, the local resin removal results in exposure of fibers to the erosive environment, as shown in the 3D profile in Figure 1c.…”
Section: Surface Analysis After Erosionmentioning
confidence: 99%
“…Based on this analysis, it was assumed that the wet pulverization of CWF L not only reduced the particle size, but also assisted in causing fibrillation on the WF particle surfaces, which ensured more interfacial interaction between wood flour and PP matrix. Moreover, fatigue life of composites increased with increasing particle aspect ratio, as did tensile strength [41].Hence, the fatigue test results of CWF L composites indicated that the wet pulverization of WF increased the particle aspect ratio of wood flour. This result was in good agreement with the measured aspect ratio values of CWF L .…”
Section: Fatigue Behavior Of Compositesmentioning
confidence: 92%